Concept and its Linguacultural Features in the Uzbek Language (Intersections of Faith and Culture: American Journal of Religious and Cultural Studies (2993-2599), 2025)
The basic unit of linguacultural studies is a cultural concept, i.e. a multidimensional semantic formation in which value, figurative and conceptual aspects are distinguished. The expression of a concept is the entire set of linguistic and non-linguistic means that directly or indirectly illustrate, explain and develop its content. The article examines the concept and its linguacultural features in the Uzbek language.